Pengaruh Dukungan Sosial dan Pengakuan Prestasi Terhadap Kepuasan Kerja Karyawan - Agus Setiono (Jurnal Bisnis dan Kewirausahaan, 2024)
This study examines the impact of social support and recognition of achievement on employee job satisfaction in Indonesia. Job satisfaction is crucial for organizational success, influencing productivity, retention, and overall performance. While many studies focus on financial factors like salary, this research emphasizes non-financial factors, such as social support from colleagues and supervisors and recognition of achievements. Using a quantitative approach, data were collected through questionnaires from 86 employees across various sectors. Multiple regression analysis was conducted to evaluate the influence of both independent variables on job satisfaction. The results indicate that both social support and recognition of achievement significantly and positively affect employee job satisfaction, with social support showing a stronger influence. These findings highlight the importance of fostering a supportive work environment and implementing recognition programs to enhance employee satisfaction. The study contributes to the literature by addressing the gap in research on non-financial factors in job satisfaction, particularly in the Indonesian context. Future research should explore this relationship further using mixed methods and consider moderating variables such as organizational culture.